(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Increasing organic formation in the country is dependent on the availability of organic input andoutput. To improve organic production in India, a more sophisticated marketing infrastructure is urgentlyrequired. This paper made a sincere effort to explore how Indian consumers feel about organic productsand their marketing. Based on the data, it appears that the majority of consumers, especially those livingin cities, have a strong preference for organic food. Demand for organic products is rising, but supply isextremely low because of the area’s poor marketing of organic goods. Many factors contribute to thisproblem, including a dearth of organic farmers, a retail sector with too few outlets, a failure to educateconsumers, and so on. If both farmers and the government in India are serious about promoting organicfarming, then the country’s marketing infrastructure will flourish. Many people’s perspectives onproducts and services have shifted as a result of the COVID-19 epidemic. They are becoming more andmore cognizant of the perils of disregarding Earth’s needs. There was already a trend toward greaterenvironmental awareness and sustainability before the pandemic, but the spread of COVID-19 hasexpedited this trend and inspired many more individuals to take action. To that end, the health problemmay increase demand for organic foods, which are those that are not genetically modified and areinstead grown using sustainable farming practices. Understanding the habits of these organic foodpurchasers is crucial for stores looking to cater to them.